Evaluasi Penggunaan Antibiotik pada Pasien ISPA Non-pneumonia di Puskesmas Senduro Kabupaten Lumajang Tahun 2019 - Pratiwi, Permata Sari; Rachmawati, Ema; Rachmawati, Sinta; Aryani, Dhita Evi; Norcahyanti, Ika; Machlaurin, Afifah; Muhammad Hilmi Afthoni (Journal of Agropharmacy, 2024)
Acute Respiratory Infection (ARI) is an infectious disease of the upper and lower respiratory tract. Non-pneumonic ARI is mostly caused by viral infections so symptomatic therapy can be given, but it can also be caused by bacterial infections so antibiotic therapy is needed. Unwise use of antibiotics can increase bacterial resistance, thereby increasing morbidity and mortality rates. Regular evaluations need to be carried out to reduce the unwise use of antibiotics. The evaluation method that can be used is a quantitative method (ATC/DDD) to determine trends in antibiotic use. This research was conducted on 278 outpatient non-pneumonic ARI patients at the Senduro Lumajang Community Health Center in 2019, with the aim of knowing patient characteristics, antibiotic use profile, and description of antibiotic use using the ATC/DDD method. The results showed that female patients (n=154; 55.4%), were more dominant than male (n=124; 44.6%), patients with the highest age range being 36-45 years (n=70; 25, 2%), the highest diagnosis of ARI was other acute infections of the upper respiratory tract (J06) (n=147; 52.9%), the most commonly used antibiotic was amoxicillin (n=227; 81.6%) and the most rarely used was cefadroxil (n=13; 4.7%). Based on the evaluation results using the ATC/DDD method, it shows that amoxicillin is the antibiotic with the highest DDD value of 7.5 DDD/1000 patients/day and the antibiotic levofloxacin with the lowest DDD value of 0.3 DDD/1000 patients/day.